The Rhythm of the Vocal Level and its indications in Hijaziat Al-Sharif Al -Radi (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research discusses the rhythms of the vocal level in Hijaziat Al-Sharif Al-Radi (406 A.H), by firstly presenting an introduction to the “rhythm” terminology through many philosophers and critics. Then, moving to the elements of rhythms of the vocal level in Alhijaziat expressed in stanzas, stress and rhythmic units through presenting a summary of every element followed by empirical research to explain the role in rhythmic stanzas and to what extent they reflect the psychological rhythm of the poet. يتناول البحث الإيقاع الصّوتي في حجازيّات الشّريف الرّضي (ت406هـ), فيبدأ بتقديم لمحة حول مصطلح الإيقاع لدى بعض الفلاسفة والنّقاد, ثم ينتقل لدراسة عناصر الإيقاع الصّوتي في الحجازيّات ممثّلة بالمقاطع والنّبر والوحدات الإيقاعيّة وذلك من خلال تقديم موجز نظري حول كلِّ عنصر متبوعاً بدراسة تطبيقيّة لبيان دور هذه العناصر في إيقاعيّة تلك النّصوص ومدى تجسيدها للإيقاع النّفسي لدى الشّاعر.